Extension for Community Healthcare Outcomes (ECHO) Chronic Pain & Opioid Stewardship in Northwestern Ontario: A Thematic Analysis of Patient Cases - Patricia A. Poulin; Yaadwinder Shergill; Adrian Grebowicz; Inês Almeida; Rosemee Cantave; Bryan MacLeod; Tim Larocque; Donna Garstin; Sarah F. Fitzgerald; Joshua A. Rash (Taylor & Francis Group, 2022)
Background Chronic pain (CP) is a debilitating disease that reduces quality of life, decreases productivity, and has become a primary cause of health care resource consumption. Despite this, many Canadian family physicians have received little formal education in managing CP, making it one of the most challenging areas of practice in primary care. Project Extension for Community Healthcare Outcomes Chronic Pain & Opioid Stewardship St. Joseph's Care Group (Project ECHO-SJCG) is an evidence-based educational program connecting community-based health care providers (HCPs) with an interprofessional team by videoconference to learn about management of CP in rural, remote, and underserved areas.Aims To explore key learning points from cases presented at Project ECHO-SJCG, identify and analyze themes and improve future sessions of continuing professional development for HCPs.Methods We completed a thematic analysis of forty cases and key learning points using the constant comparison method. We also summarized descriptive statistics for patient and provider characteristics.Results Forty cases were presented by 31 HCPs, who received suggestions focused on assessment and diagnosis, pharmacological and non-pharmacological pain symptom management, interventional management, attention to biopsychosocial factors, and appropriate referral to other HCPs.Conclusion Project ECHO-SJCG cases allow HCPs to gain a broad knowledge base to evaluate and manage CP in their practice. Identified themes highlight common gaps in HCPs' knowledge and will guide future sessions.